Diversity and temporal activity patterns of Diptera associated with captive wild mammals and the efficency of trapping methods - Ho, Jessie Si Wai (2015)
Diptera are arthropods of veterinary and medical importance as a large number are efficient vectors of diseases for both animals and humans. This study was conducted to determine the diversity, abundance and activity patterns of Diptera associated with captive wild mammals at a local zoo, as well as the efficiency of five different fly traps (Nzi, Malaise, Intercept, CDC-UV, and CDC-CO2). A total of 1800 trap hours were conducted in the enclosure vicinity of six different species of wild mammals (Ankole Cattle, Spotted Deer, Asian Elephant, White Rhinoceros, Barking Deer and Tapir). The traps were placed approximately 10m apart and checked at intervals of three hours and twelve hours respectively from 0700 – 1900hrs, and subsequently left overnight to determine the night catch. The captured flies were killed using ethyl acetate, dry mounted and examined under a stereomicroscope. Identification of the flies was done following published taxonomic keys. Six families of Diptera (Ceratopogonidae, Culicidae, Psychodidae, Muscidae, Sarcophagidae and Calliphoridae) comprising 17 genera, were encountered in this study. Twenty species of mosquitoes (Culicidae) were trapped, of which Culex quinquefasciatus, and Aedes albopictus were dominant. Biting midges (Culicoides peregrinus, Culicoides gutiffer and Culicoides actoni) and sand flies (Sergentomyia spp.) were also encountered. The majority (90%) of the filth flies were from the genus Musca, followed by Stomoxys and Sacrophaga. The Nzi traps collected a significantly (p<0.05) higher number of large flies compared to Malaise and Intercept traps. The CDC-UV traps caught 73% more mosquitoes compared to those baited with carbon dioxide. There was an ascending diurnal activity pattern for the large flies, which peaked from 1600-1900hrs. The mosquitoes on the contrary, were mostly nocturnal with peak activity observed from 1900-0700hrs. The high diversity and abundance of Diptera associated with captive wild mammals is of concern as these arthropods may act as vectors of many haemoparasites and viruses. In addition, the possibility of vector-borne zoonotic disease transmission warrants attention as the zoos provide a close interface between wild animals, humans and disease vectors.